Distribution and genotype-phenotype correlation of GDAP1 mutations in Spain - Sivera, Rafael; Frasquet, Marina; Lupo, Vincenzo; García-Sobrino, Tania; Blanco-Arias, Patricia; Pardo, Julio; Fernández-Torrón, Roberto; de Munain, Adolfo López; Márquez-Infante, Celedonio; Villarreal, Liliana; Carbonell, Pilar; Rojas-García, Ricard; et al. (Scientific reports, 2017)
Mutations in the GDAP1 gene can cause Charcot-Marie-Tooth disease. These mutations are quite rare in most Western countries but not so in certain regions of Spain or other Mediterranean countries. This cross-sectional retrospective multicenter study analyzed the clinical and genetic characteristics of patients with GDAP1 mutations across Spain. 99 patients were identified, which were distributed across most of Spain, but especially in the Northwest and Mediterranean regions. The most common genotypes were p.R120W (in 81% of patients with autosomal dominant inheritance) and p.Q163X (in 73% of autosomal recessive patients). Patients with recessively inherited mutations had a more severe phenotype, and certain clinical features, like dysphonia or respiratory dysfunction, were exclusively detected in this group. Dominantly inherited mutations had prominent clinical variability regarding severity, including 29% of patients who were asymptomatic. There were minor clinical differences between patients harboring specific mutations but not when grouped according to localization or type of mutation. This is the largest clinical series to date of patients with GDAP1 mutations, and it contributes to define the genetic distribution and genotype-phenotype correlation in this rare form of CMT.